A study on optimization model for production-distribution problem with constraints - Lim, Seokjin; Park, Myon-Woong (WMSCI 2006: 10TH WORLD MULTI-CONFERENCE ON SYSTEMICS, CYBERNETICS AND INFORMATICS, VOL I, PROCEEDINGS, 2006)
Most companies in today's competitive business environment have made significant changes in their managing operations. Supply chain management (SCM) has become one of the most important methods of competitive advantage in business environment today Recently, a multi-facility, multi-product and multi-period industrial problem has been widely investigated in SCM. One of the key issues in the current SCM research area involves reducing both production and distribution costs. The purpose of this study is to determine the optimal quantity of production and transportation with minimum cost in supply chain network. We have presented a mathematical model that deals with real world factors and constraints. The developed optimization model tackles the above problems under the restricted conditions such as transportation time and quantity of inventory. Computational experiments using commercial linear programming tool show that the real size problems we encountered can be solved in reasonable time.